(untitled) (Marketing Journal, 2025)
This article analyzes the opportunities and prospects of using digital marketing in Uzbekistanʼs fashion industry. It examines brand promotion through social media, mobile applications, websites, influencer marketing, and artificial intelligence -based technologies. These tools are shown to accelerate market entry and help establish strong customer relationships. Based on digital strategies, the paper suggests directions for sustainable growth for fashion brands. 242